Risperidone as a treatment for childhood habitual behavior - Victoria Omranifard; Mostafa Najafi; Mohammad Reza Sharbafchi; Parisa Emami; Mohammad Maracy (Wolters Kluwer Medknow Publications, 2013)
Objective: The aim of this study was to investigate the effect of adding risperidone to the general behavioral treatment of masturbation in children 3-7 years old. Methods: A 4 week randomized clinical controlled trial was designed in year 2009. Samples have been chosen from children who have been referred to the Child and Adolescence Psychiatric Clinic of Isfahan University of Medical Sciences. Ninety children were recruited at the study and randomly allocated into the risperidone and control groups (44 and 46 respectively). The risperidone group was medicated simultaneously by behavioral treatments and 0.25-1 mg of risperidone daily while the controls only received the behavioral treatments. Findings: The mean ± SD age of the risperidone and control groups was 5.3 ± 1.1 and 4.9 ± 1.1 years, respectively. The mean ± SD of the period of suffering from masturbation was 3.4 ± 1.2 and 3.8 ± 1.7 months in the risperidone and the control groups, respectively. At the beginning of the study, the mean frequency of masturbation in control and the risperidone groups was 2.6 ± 0.9 and 2.7 ± 0.9 times/day, whereas after the 4 th week, it decreased to 1.4 ± 0.6 and 1.1 ± 0.5 times/day, respectively. The results showed a more reduction in the mean frequency of masturbation in the risperidone group significantly. Conclusion: In comparison to the general behavioral treatment, risperidone in addition to the behavioral treatment will probably reduce the frequency of masturbation in children more effectively.